Capturing the fungal community associated with conventional and organic Trebbiano Abruzzese grapes and its influence on wine characteristics. (April 2023) - Rossetti, Alessio Pio; Perpetuini, Giorgia; Battistelli, Noemi; Zulli, Camillo; Arfelli, Giuseppe; Suzzi, Giovanna; Cichelli, Angelo; Tofalo, Rosanna
Abstract: In this study, the influence of conventional and organic managements on Vitis vinifera cv. Trebbiano Abruzzese on fungal community was investigated. Moreover, spontaneous vinifications were performed, and wines were characterized for some oenological parameters and aroma profiles. A core of 8 genera was detected ( Zygosaccharomyces spp., Cladosporium spp., Botrytis spp., Hanseniaspora spp., Pichia spp., Alternaria spp., Candida spp., Aureobasidium spp.), while some genera were unique for each grape sample. Saccharomyces spp. and Mucor spp. were present only on conventional grapes, while Penicillium spp. and Aspergillus spp. only on organic ones. At the species level Aureobasidium pullulans, Cladosporium cladosporioides and Pichia terricola dominated in both samples with varying abundance depending on the vineyard management. The fermentation performed with conventional grapes resulted in a faster rate than that performed with organic ones. No significative differences were observed for the oenological parameters analyzed with the only exception of ethanol content which was higher in conventional wines than in organic ones: 11.57 ± 0.10 g/L and 10.51 ± 0.09 g/L, respectively. Conventional wines were characterized by the presence of aldehydes, while organic ones by terpenes and β-damascenone. The obtained results suggested an effect of vineyard practices on grape fungal community which could in turn influence some characteristics of Trebbiano d'Abruzzo wines. Highlights: Farming practices influenced Trebbiano Abruzzese grape fungal community. Fermentations performed with conventional grapes showed a fastest rate. Conventional and organic wines showed a similar physical-chemical profile. Conventional wines were rich in aldehydes. Organic wines were rich in terpenes, and β-damascenone.